Optimizing inventory-ordering policies in supply chain management : a case study on a selected company from the Vaal Region - Ebouele, Blaise Bolan Benga (My University, 2014)
Implementing either periodic or continuous inventory review model within most manufacturing-companies-supply chains, as a management tool, incurs higher costs. These high costs affect the system flexibility which in turn affects the level of service required to satisfy customers. However, these effects are not clearly understood. This may be due to the fact that lead time and demand which are important input parameters of the manufacturing supply chain are not designed to be fully utilized under different and uncertain conditions such as seasonality, poor manufacturing, poor supplies and delivery performance, etc. Coming up with a hybrid inventory model which may combine, in some sense a continuous (r, Q) and a periodic (R, S) inventory review models can be useful in dealing with such problem. Therefore, more attention should be first devoted to formulating accurate models for lead time and demand that incorporate uncertainty. This study presents a simulation based approach that assesses the effect of uncertainty on the cost of implementing a continuous (r, Q), periodic (R, S) and hybrid inventory review models while considering appropriate constraint such as customer service and system flexibility. The stochastic representations of demand and lead time are proposed and used in the simulation models. Results reveal that under a unique situation, implementing a continuous (r, Q) inventory review model may cause manager to under-budget while the use of a periodic (R, S) inventory review models may lead to over budget and vice versa. Further investigation shows that the cost of implementing the hybrid inventory model, although higher at the beginning of operation, seems to be the most cost effective one over time. The result also reveal optimal re-order point path and optimal review interval path which when followed, should lead to optimal inventory cost path as demand and lead time fluctuate. Thus, a management guide is proposed that can be used by managers in making inventory decision.
M. Tech. (Industrial Engineering, Faculty of Engineering and Technology) Vaal University of Technology|
Keywords: Inventory review model; Hybrid inventory model; Manufacturing company supply chains; 658.757; Physical distribution of goods -- Management.; Business logistics.; Inventory control.